Barriers and facilitators of HIV and hepatitis C care among people who inject drugs in Nairobi, Kenya: a qualitative study with peer educators - Natasha T. Ludwig-Barron; Brandon L. Guthrie; Loice Mbogo; David Bukusi; William Sinkele; Esther Gitau; Carey Farquhar; Aliza Monroe-Wise (BMC, 2021)
Abstract Background In Kenya, people who inject drugs (PWID) are disproportionately affected by HIV and hepatitis C (HCV) epidemics, including HIV-HCV coinfections; however, few have assessed factors affecting their access to and engagement in care through the lens of community-embedded, peer educators. This qualitative study leverages the personal and professional experiences of peer educators to help identify HIV and HCV barriers and facilitators to care among PWID in Nairobi, including resource recommendations to improve service uptake. Methods We recruited peer educators from two harm reduction facilities in Nairobi, Kenya, using random and purposive sampling techniques. Semi-structured interviews explored circumstances surrounding HIV and HCV service access, prevention education and resource recommendations. A thematic analysis was conducted using the Modified Social Ecological Model (MSEM) as an underlying framework, with illustrative quotes highlighting emergent themes. Results Twenty peer educators participated, including six women, with 2-months to 6-years of harm reduction service. Barriers to HIV and HCV care were organized by (a) individual-level themes including the competing needs of addiction and misinterpreted symptoms; (b) social network-level themes including social isolation and drug dealer interactions; (c) community-level themes including transportation, mental and rural healthcare services, and limited HCV resources; and (d) policy-level themes including nonintegrated health services, clinical administration, and law enforcement. Stigma, an overarching barrier, was highlighted throughout the MSEM. Facilitators to HIV and HCV care were comprised of (a) individual-level themes including concurrent care, personal reflections, and religious beliefs; (b) social network-level themes including community recommendations, navigation services, family commitment, and employer support; (c) community-level themes including quality services, peer support, and outreach; and (d) policy-level themes including integrated health services and medicalized approaches within law enforcement. Participant resource recommendations include (i) additional medical, social and ancillary support services, (ii) national strategies to address stigma and violence and (iii) HCV prevention education. Conclusions Peer educators provided intimate knowledge of PWID barriers and facilitators to HIV and HCV care, described at each level of the MSEM, and should be given careful consideration when developing future initiatives. Recommendations emphasized policy and community-level interventions including educational campaigns and program suggestions to supplement existing HIV and HCV services.